2014
DOI: 10.1051/0004-6361/201423763
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a high-quality quasi-periodic rapidly propagating wave train using SDO/AIA

Abstract: Context. We present a new event of quasi-periodic wave trains observed in EUV wavebands that rapidly propagate away from an active region after a flare. Aims. We measured the parameters of a wave train observed on 7 December 2013 after an M1.2 flare, such as the phase speeds, periods and wavelengths, in relationship to the local coronal environment and the energy sources. Methods. We compared our observations with a numerical simulation of fast magnetoacoustic waves that undergo dispersive evolution and leakag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
78
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 45 publications
12
78
2
2
Order By: Relevance
“…Rather, it is based on the relationship to other periodicities and comparison with those expected for known wave modes when realistic loop and plasma properties are assumed. Zhang et al (2015) reported an observation of a coronal funnel with SDO/AIA which demonstrates fast and slow waves propagating along the same field-aligned path, consistent with numerical simulations of Pascoe et al (2013b; Nisticò et al (2014). Measurement of the propagation speeds allowed the plasma-β to be estimated as approximately 0.01.…”
Section: Introductionsupporting
confidence: 52%
“…Rather, it is based on the relationship to other periodicities and comparison with those expected for known wave modes when realistic loop and plasma properties are assumed. Zhang et al (2015) reported an observation of a coronal funnel with SDO/AIA which demonstrates fast and slow waves propagating along the same field-aligned path, consistent with numerical simulations of Pascoe et al (2013b; Nisticò et al (2014). Measurement of the propagation speeds allowed the plasma-β to be estimated as approximately 0.01.…”
Section: Introductionsupporting
confidence: 52%
“…A more detailed study of dispersive formation of fast wave trains in plasma funnels strengthened this interpretation (Pascoe et al 2013). Recent studies showed convincing consistence of numerical and observational results (Nisticò et al 2014).…”
Section: Introductionmentioning
confidence: 85%
“…3.1. The magnetic field used in our model is a potential field (see also Nisticò et al 2014) given by B " B 0 exp p´y{l 0 q rcos px{l 0 qē x´s in px{l 0 qē y s , (8) where B 0 is a constant determining the magnitude of the field and l 0 is the normalisation factor for the spatial size. The density profile for the field-aligned coronal loop is based on the generalised symmetric Epstein profile (Eq.…”
Section: Numerical Simulations Of Standing Sausage Modes In a Curved mentioning
confidence: 99%
“…For example, Oliver et al (2014) recently studied the dispersive evolution of propagating kink waves in coronal loops. The dispersion of propagating fast MHD waves has also been considered for current sheets (Edwin et al 1986;, coronal holes , and flaring active regions (Nisticò et al 2014) (see also recent review by Pascoe 2014).…”
Section: Introductionmentioning
confidence: 99%